Rancang Bangun Pendeteksi Gerak Menggunakan Metode Image Subtraction Pada Single Board Computer (Sbc) - Perkasa, Therzian Richard; Widyantara, Helmy; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
Abstract: Â Motion detection has been widely used in security systems on an individual or group. But there are some problems if a mounted camera and recording in realtime while there is no movement or event that occurs, namely the wasted memory. It needs a CPU (central processing unit) that require power and considerable cost, to a process of image processing. In addition, if seen from the aspect of the room, the CPU is more bulky. One alternative to overcome this problem is to design a software that can improve the efficiency of the camera, so that the camera will only detect and record when there is motion or moving objects. In this research, the author uses one single board computer i.e. Raspberry Pi to detect a movement, so that the system can be further used as a security system. Raspberry Pi is small computer credit card sized. So the user does not need more room and power to build a system of motion detection. For motion detection, the author will use image subtraction method, namely the reduction of differences between frames (fi) with the previous frame (fi-1) so that the movement is in the area of radar cameras can be detected and the results of the motion detection will be stored in an image file on a single board computer.